Mediasi Kepuasan Kerja dan Stres Kerja pada Hubungan antara Self-efficacy dan Kinerja Penjual Jasa Asuransi - Eny Sulistyowati; Susi Widjajani (Jurnal Maksipreneur, 2012)
The purpose of this research is to examine the relationship between selfefficacy and job performance; job satisfaction and job stress as a mediating variable. This research also investigates the impact of job satisfaction on job performance and job stress on job performance. Variables in this research were measured with a survey of 109 insurances salespersons in Yogyakarta and Semarang. Path Analysis were used to examine the effects of self-efficacy and job performance, job satisfaction on job performance, and job stress on job performance. Results showed that the relationship showed that self-efficacy significantly related to job satisfaction and performance, but no significant relationship existed with job stress. It also showed that job satisfaction partially mediated the relationship between self-efficacy and job performance. In addition, this research found that job stress not mediated the relationship between self-efficacy and job performance. There is no significant relationship existed between job stress and job performance but this research showed that job satisfaction significantly related to job performance.